Pengaruh Terapi Murottal Al-Qur’an terhadap Penurunan Intensitas Nyeri Persalinan Kala 1 Fase Aktif Dilatasi Maksimal: The Influence of Murottal Al-Qur’an Therapy to Decrease In The Intensity of the Pain of Labor When I Phase of Active Maximum Dilatation - Ayu Safitri; Artika Dewie; Niluh Nita Silvia (Poltekkes Kemenkes Palu, 2021)
Introduction: Pharmacological and non-pharmacological techniques are methods used to reduce labor pain. Non-pharmacological techniques in the form of distraction by listening to the murottal Al-Qur'an can be an option. The purpose of this study was to determine the effect of murottal Al-Qur'an therapy on reducing the intensity of labor pain during the 1st active phase. Method: The type of research used in this study was Pre Experiment, one group pretest-posttest research design. The population in this study were mothers who gave birth at the first stage of Sriwati PMB with a sample of 15 people. The pain was measured using the Numeric Rating Scale (NRS). Statistical analysis used the Wilcoxon Signed Rank Test with a confidence level of 95% (α = 0.05). The result of the statistical test, the value of p=0.001, which means that there is a significant difference in labor pain in women who give birth before and after listening to the Murottal Al-Qur'an. It is suggested to do non-pharmacological techniques to listen to Murottal Al-Qur'an as one of the techniques to reduce the first stage labor pain at PMB Sriwati.